State laws matter when it comes to school provisions for structured PE and daily PE participation. Issue 2 (2nd March 2020) - Piekarz-Porter, Elizabeth; Lin, Wanting; Leider, Julien; Turner, Lindsey; Perna, Frank; Chriqui, Jamie F
Abstract: The physical and mental benefits children receive from physical activity have been well documented, and physical education is a key way to ensure that physical activity opportunities are available during the school day. This study evaluates whether state PE laws are associated with school-level practices of requiring structured PE classes and whether students take PE classes daily. State laws were obtained as part of the National Cancer Institute's Classification of Laws Associated with School Students (CLASS) and were compiled for all 50 states and District of Columbia using Boolean keyword searches in LexisAdvance and WestlawNext. PE time requirements and state daily PE requirements in the laws were subsequently linked to school-required structured PE classes and daily PE in the School Nutrition and Meal Cost Study (SNMCS) Principal Survey. Logistic regression analyses were conducted while controlling for grade level, district child poverty rate, district race/ethnicity, school urbanicity, and school size. The state daily PE analysis also controlled for region. Schools located in a state that required at least 90 min of PE per week at the elementary level or 150 min of PE per week at the middle or high school levels had almost seven times higher odds of requiring structured PE. Schools located in a state that required daily participation of PE had almost five times higher odds of at least some students taking PE daily. State policymakers can utilize these findings to promote laws that require time for PE every week, daily if possible.